Functional correlation of genome‐wide DNA methylation profiles in genetic neurodevelopmental disorders. Issue 11 (21st August 2022) - Levy, Michael A.; Relator, Raissa; McConkey, Haley; Pranckeviciene, Erinija; Kerkhof, Jennifer; Barat‐Houari, Mouna; Bargiacchi, Sara; Biamino, Elisa; Palomares Bralo, María; Cappuccio, Gerarda; Ciolfi, Andrea; Clarke, Angus; et al.
Abstract: An expanding range of genetic syndromes are characterized by genome‐wide disruptions in DNA methylation profiles referred to as episignatures. Episignatures are distinct, highly sensitive, and specific biomarkers that have recently been applied in clinical diagnosis of genetic syndromes. Episignatures are contained within the broader disorder‐specific genome‐wide DNA methylation changes, which can share significant overlap among different conditions. In this study, we performed functional genomic assessment and comparison of disorder‐specific and overlapping genome‐wide DNA methylation changes related to 65 genetic syndromes with previously described episignatures. We demonstrate evidence of disorder‐specific and recurring genome‐wide differentially methylated probes (DMPs) and regions (DMRs). The overall distribution of DMPs and DMRs across the majority of the neurodevelopmental genetic syndromes analyzed showed substantial enrichment in gene promoters and CpG islands, and under‐representation of the more variable intergenic regions. Analysis showed significant enrichment of the DMPs and DMRs in gene pathways and processes related to neurodevelopment, including neurogenesis, synaptic signaling and synaptic transmission. This study expands beyond the diagnostic utility of DNA methylation episignatures by demonstrating correlation between the function of the mutated genes and the consequent genomic DNA methylation profiles as a key functional element in the molecular etiology of genetic neurodevelopmental disorders.